Influence of visceral fat in the outcomes of colorectal cancer - Goulart, André (2019)
Aim: To determine the relationship of visceral fat (VF) with the surgical outcome of the patients with colorectal cancer (CRC) submitted to curative surgery. Methods: Retrospective analysis of all patients submitted to CRC surgery during 3 years with a minimum of 5 years of follow-up. We assessed the length of hospital stay, complications, pathologic reports, surgical re-interventions and hospital re-admissions, relapses, survival time and disease-free time. VF was calculated based on patients' pre-operative CT-scan. The patients were divided into quartiles according to the VF area. Linear regression models and logistic regression models were used to establish a relationship between VF and all data collected. Results: The study included 199 patients (129 with colon cancer [CC] and 70 with rectal cancer). The average area of VF was 115.7 cm(2). Patients with CRC revealed a direct relationship between VF and postoperative complications (p = 0.043), anastomotic leakage (p = 0.009) and re-operation (p = 0.005). The subgroup of patients with CC had an inverse as-sociation between VF and lymph nodes harvested (p = 0.027). Survival analyses did not reveal significant differences. Conclusion: VF has an influence on postoperative complications, anastomotic leakage and re-operation. A negative influence of VF on lymph nodes harvested was observed on CC patients.